Religion Pluralism: Meeting Point Looking For Religions - Siti Juwariyah (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
Religious plurality actually necessitates religious pluralism. That is an understanding that promotes and upholds the attitude of accepting, maintaining, and respecting religious diversity and diversity as uniquely true to its Adherents. But reality speaks differently. Religious pluralism precisely presents a prolonged polemic between pro and contra groups. Religious pluralism is transformed into something very complicated. Religious pluralism can not be understood simply by saying that our society is advanced, God has created us with different religions, nationalities, tribes, and others. In fact, we often experience Bloodshed tragedies in the name ofreligion, Such as: Ciukesik, Magelang, clash of Monas monument between FPI and AKKBB, as well as of bloody events. However, to borrow the word Cak Nur, religious pluralism must be understood as a true link of diversity in bonds. Even religious pluralism is a must for human safety and world peace.On that basis, the question arises: Can religious pluralism, be used as a way to find the meeting point of religions in the Midst of religious conflict?Keywords: Religion; Pluralism; Conflict.